2018
DOI: 10.1007/s00737-018-0862-x
|View full text |Cite
|
Sign up to set email alerts
|

A mindfulness intervention to reduce maternal distress in neonatal intensive care: a mixed methods pilot study

Abstract: Mothers with an infant in the neonatal intensive care unit (NICU) are at risk for depression, anxiety, and trauma symptoms, with negative implications for maternal-infant bonding, maternal well-being, and infant development. Few interventions to promote NICU mothers' mental health, however, have been developed or tested. This pre-post pilot study assessed feasibility, acceptability, and preliminary outcomes of a mindfulness intervention for NICU mothers. Twenty-seven mothers were recruited from a university NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…Some are mainly based on cognitive therapy and parent-oriented discharge education 21,22 . Others aim to decrease parental stress with spiritual care 23 , mindfulness 24 , and relaxation 25 .…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Some are mainly based on cognitive therapy and parent-oriented discharge education 21,22 . Others aim to decrease parental stress with spiritual care 23 , mindfulness 24 , and relaxation 25 .…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Mindfulness-based interventions are emerging as successful interventions to reduce perinatal stress and improve perinatal mental health outcomes, such as depression and anxiety (Dhillon et al, 2017; Hughes et al, 2009; Lever Taylor et al, 2016; Matvienko-Sikar et al, 2016; Mendelson et al, 2018; Shi & MacBeth, 2017). Mindfulness has been defined by Jon Kabat-Zinn as the “awareness that arises through paying attention, on purpose, in the present moment, non-judgmentally, in the service of self-understanding and wisdom” (Kabat-Zinn, 1996).…”
Section: Perinatal Stress and Intersectionality In African-american Wmentioning
confidence: 99%
“…Mindfulness has been defined by Jon Kabat-Zinn as the “awareness that arises through paying attention, on purpose, in the present moment, non-judgmentally, in the service of self-understanding and wisdom” (Kabat-Zinn, 1996). Mindfulness-based interventions used in the perinatal period include mindfulness-based stress reduction, mindfulness-based cognitive therapy, and integrated mindfulness yoga (Dhillon et al, 2017; Hughes et al, 2009; Lever Taylor et al, 2016; Matvienko-Sikar et al, 2016; Mendelson et al, 2018; Shi & MacBeth, 2017; Tellhed et al, 2019; Zhang & Emory, 2015). Mindfulness-based stress reduction is a structured eight-week program teaching ways of mindful meditation to reduce physical and psychological symptoms of stress (Grossman et al, 2004; Kabat-Zinn, 2013).…”
Section: Perinatal Stress and Intersectionality In African-american Wmentioning
confidence: 99%
“…It is well proven that having an infant in the neonatal intensive care unit(NICU) is highly stressful and exposes parents at risk to trauma symptoms (1)(2)(3). Parenting stress in NICU is defined as an imbalance between expectations, perceived resources and demands of caregiving(4) and originates not only from uncertainty regarding neonate's baseline condition and prognosis but also from medical problems, because these babies are at greater risk of infection and nutritional problems (5) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Infants in the NICU are usually less accessible to the mother because of the monitor leads, tubes for feeding and breathing and NICU itself experienced as the stressful, noisy and cold environment. In addition, mothers in the NICU are in the postpartum period that is accompanied by hormonal changes, family role changes, new responsibilities, fatigue and sleep problems (6). Previous studies showed that high level stress experienced by mothers in the NICU is associated whit depression, anxiety (7), symptoms of acute stress disorder and posttraumatic stress disorder in them (1)(2)(3) 3…”
Section: Introductionmentioning
confidence: 99%